ANALISIS KOMPARATIF KINERJA KEUANGAN SEBELUM DAN SESUDAH AKUISISI PADA INDUSTRI BARANG KONSUMSI - Mutiara, Indah (JURNAL RISET AKUNTANSI JAMBI, 2017)
The purpose of this research is to know the condition of financial performance of consumer goods industry companies listed in Indonesia Stock Exchange based on profitability ratios (NPM, ROA, ROE) and market ratio (EPS, BV) before and after acquisition and to know comparison of financial performance consumer goods companies listed on the Indonesia Stock Exchange (IDX) based on profitability ratios (NPM, ROA, ROE) and market (EPS, BV) before and after the acquisition The results of this study indicate: (1) Based on the financial performance of consumer goods industry companies listed under Indonesian securities using NPM variables, ROA and ROE both before and after the acquisition can be concluded there is no significant difference. (2) By using Wilcoxon Signed Ranks Test method on financial performance of consumer goods industry companies listed in Indonesian stock securities either from observation period comparing between 3 years before with 1 year to 3 years after acquisition, showed no significant difference between before and after acquisitions with a significance level greater than 0.05.